1967
DOI: 10.3181/00379727-124-31703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acetoacetate and  -Hydroxybutyrate on Vitamin B12 in Rats

Abstract: The intermediary compounds involved in blood urea and inorganic phosphate (4). These fat metabolism, acetoacetate and P-hydroxy-ketone bodies also showed increased cholesbutyrate on prolonged administration have terol/phospholipid ratio ( 5 ) , disturbances in been shown to cause increase in bloo'd sugar the balance of hepatic glycogenesis and ( 1 ), blood lactic and pyruvic acids ( 2,3), and glycogenolysis ( 6), decrease in reduced at UNIV OF MICHIGAN on June 26, 2015 ebm.sagepub.com Downloaded from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1967
1967
1970
1970

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Saturated fats have also been shown to be more ketogenic than the unsaturated ones (12). Recently ketone bodies have been found to increase the vitamin B12 requirement in rats (11). In the present investigation also the same relationship between vitamin B12 and ketone bodies is observed.…”
Section: And Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Saturated fats have also been shown to be more ketogenic than the unsaturated ones (12). Recently ketone bodies have been found to increase the vitamin B12 requirement in rats (11). In the present investigation also the same relationship between vitamin B12 and ketone bodies is observed.…”
Section: And Discussionsupporting
confidence: 76%
“…Severity of vitamin B12 deficiency has also been shown to increase by increasing the fat content of the diets (10). Fat intermediate meta bolites, ketone bodies, have recently been shown to cause depletion of vitamin B12 in blood and liver of rats (11). Further, saturated fats have been found to be more ketogenic than the unsaturated ones (12).…”
mentioning
confidence: 99%
“…Nath and Nath (10) have demonstrated a significant decrease in vitamin B12 levels in ketone bodies injected animals. It was also found that the effect of various high fat diets on the levels of this vitamin varied in accordance with their ketogenic petency.…”
Section: And Discussionmentioning
confidence: 99%
“…GCA, which has been shown to maintain the reduced glutathione level (28,29), might possibly prevent the inhibition of these enzymes by retaining the normal level of reduced glutathione of the cell.…”
Section: Resultsmentioning
confidence: 99%